Analysing mechanisms for meeting global emissions target: A dynamical systems approach - Shyam Ranganathan; Ranjula Bali Swain (Uppsala University, Department of Economics, 2014)
Global emissions beyond 44 gigatonnes of carbondioxide equivalent (GtCO2e) in 2020 can potentially lead the world to an irreversible climate change. Employing a novel dynamical system modeling approach, we predict that in a business-asusual scenario, it will reach 61 GtCO2e by 2020. Testing estimated parameters, we find that limiting the burden of emission reduction to the top 25 global emitters, does not increase their encumbrance. In absence of emission cuts, technology and preferences for environmental quality have to improve by at least 2.6 percent and 3.5 percent if the emission target has to be met by 2020.
urn:nbn:se:uu:diva-235543
Keywords: C51; C52; C53; C61; Q01; Q50; 330; Sustainable Development Goals; dynamical systems; Bayesian; greenhouse gases